Hepatite B na Síndrome de Imunodeficiência Adquirida - Tibúrcio, Alberto Saraiva; Azevedo, Kátia Martins Lopes de; Passos, Mauro Romero Leal (Brazilian Journal of Sexually Transmitted Diseases, 1996)
Seventy-three pat.ients with Acquired lmmunodeficicncy Syndrome (AIDS), admítted to the infectious and Parasitic Diseases Ward at Hospital Universitário Antônio Pedro in Niterói, from April, 10th 1985 to April, 10 th, 1993, were retrospectively studicd. Of these 73 patients, 52 (71,2%) had serological evidence or infcction with thc hepatitis B virus (HBV). Artcr a review of the literature about the possible intcractions of AIDS with hepatitis B anel othcr sexuality trnnsmitted discases (STD), an analysis of thc epidemiological profile of all 73 patients enrolled in lhe study was pcrfonned. Thc author highlights the importance of scrcening HIV carriers or AIDS patients for hepatitis B and other STD, aiming to establish a strategy for the prophylaxis of hepalitis B on these people, etither by sanitary education, or by aclive and passive immunization.